KECURANGAN LAPORAN KEUANGAN (FRAUDULENT) SEKTOR TAMBANG DI INDONESIA - Imam Wahyudi; Soelistijono Boedi; Abdul Kadir (KRISNA: Kumpulan Riset Akuntansi, 2022)
This research is entitled Fraudulent Mining Sector Report in Indonesia. This type of research uses a quantitative approach. The data used in this study are the annual financial statements of mining companies listed on the Indonesia Stock Exchange in 2014-2019. The analytical tool used in this research is the path analysis test with the WarpPls application. The results of the study indicate that financial stability and the nature of industry have an effect on fraudulent financial statements. On the other hand, external pressure, personal financial need, effective monitoring, and an independent board of commissioners have no effect on fraudulent financial statements